Iowa Birdline update, August 27, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Iowa Birdline update for August 27, 1990. Highlights of the update include sightings of Barn Owls, an immature Bald Eagle, Peregrine Falcons, and a family of Blue Grosbeaks. Also of note were the large numbers of shorebirds, Herons, Egrets, and Warblers. Epson - sheet feed/flatbed